Terra sigillata from Baracs settlement in Pannonia Inferior - Hajdu, Barbara (Rei Cretariae Romanae Fautorum Acta, 2022)
This paper presents the terra sigillata findings of Baracs, a Roman era settlement in Pannonia Inferior, as well as the composition of the pottery sherds and their statistical and chronological analysis. The settlement’s period of flourishment can be estimated to between the second half of the 2nd century AD and the middle of the 3rd century AD.